Adaptive scaling framework for system transformation in One CGIAR - CGIAR Research Program on Water, Land and Ecosystems (2021)
Adaptive scaling framework is applied in scaling of farmer-led irrigation development, climate smart agriculture, agro-ecological agriculture projects and programs implemented by IWMI and other partners